The Impact of ‘Stay At Home’ Orders on Emergency Room Admissions - Kocak, Abdullah Osman; Dogruyol, Sinem; Akbas, Ilker; Kerget, Bugra; Akgol Gur, Sultan Tuna; Cakir, Zeynep (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. The 2019-novel-coronavirus (2019-nCoV) outbreak has become a common problem for the whole world. Aim. To investigate the impact of the 2019-nCoV pandemic period in our country on emergency room admissions. Materials and methods. The study was designed as a retrospective cohort. The first case of pneumonia infected with nCoV in our country was diagnosed on March 11, 2020. Considering the date of March 11, 2020, emergency room admissions for two periods of 7 days were investigated, pre-COVID-19 and COVID19. Demographic data, admission diagnosis, vital findings, stay times in emergency room, terminations and emergency department mortality examined. A group of ‘geriatric’ patient populations were created to examine the admission characteristics of patients aged-65 and over. Results. The 3466 patients included in the study. The average number of daily admissions was significantly higher in the pre-COVID-19 period (350.4 ± 54.5), compared to the COVID-19 period (144.7 ± 20.2, p=0001). While the proportion of cardiac- caused admissions increased during the COVID period, the proportion of gastrointestinal-induced admissions decreased (p<0001). Hospitalization rates for both adult and geriatric patients increased during the COVID period (p<0001). Conclusion. Despite all the negativity caused by the outbreak, this period has been one in which the public is aware of unnecessary emergency room which has been subsequently lessened.
Keywords: Covid-19; emergency visits; geriatric patients